Cardiovascular and respiratory outcome of preconditioned rats submitted to chronic intermittent hypoxia. Issue 9 (September 2015) - Perim, Raphael R.; Bonagamba, Leni G. H.; Machado, Benedito H.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? What are the effects of hypoxic preconditioning upon the cardiovascular and respiratory responses to subsequent episodes of chronic intermittent hypoxia? What is the main finding and its importance? The cardiovascular and respiratory responses to a chronic intermittent hypoxia protocol were not altered by previous exposure to intermittent or sustained hypoxia. These findings show that preconditioning to hypoxia produced neither facilitation nor protection from the cardiovascular and respiratory dysfunctions in response to subsequent episodes of chronic intermittent hypoxia in juvenile rats. Rats exposed to chronic intermittent hypoxia (CIH) develop hypertension, which is associated with changes in the coupling of sympathetic and respiratory activities. In this study, we hypothesized that previous preconditioning to intermittent or sustained hypoxia would affect cardiovascular and respiratory changes produced by subsequent protocols of CIH. To test this hypothesis, male Wistar rats were preconditioned to either 10 days of CIH or 24 h of sustained hypoxia (SH). After the initial exposure to hypoxia, rats were maintained in normoxic conditions for 15 days before a new protocol of CIH during 10 days. Cardiovascular and respiratory variables obtained from groups of preconditioned rats were compared with a group of rats exposed to CIH for the first time and also to a group of rats maintained in normoxic conditions throughout the period of time of the respective preconditioning protocol. The data show that CIH produced a similar increase in arterial pressure and heart rate in both CIH and SH preconditioning protocols. Respiratory parameters during basal conditions were also not affected by preconditioning to either CIH or SH. We conclude that previous exposure to CIH or SH preconditioning does not facilitate or prevent the cardiovascular changes produced by CIH.